Cobalt-manganese-strontium ternary metal catalyst as well as preparation method and application thereof
By developing cobalt, manganese, strontium ternary metal catalysts, the problem of existing electrocatalysts being easily dissolved in strong acid environments has been solved, and the acidic OER catalytic effect with high activity and stability has been achieved, and the advancement of electrolytic hydrogen production technology has been promoted.
Patent Information
- Application Number
- CN202411014587.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-07-26
AI Technical Summary
Existing electrocatalysts are easily oxidized and dissolved under strong acid environments and high anode potentials, and precious metal materials are scarce, which limits the practical application of hydrogen production by electrolyzing water.
A cobalt, manganese, strontium ternary metal catalyst was developed. The material surface was rough and there were holes, including MnO2, Co3O4, and SrO2 phases. By changing the ratio of Mn, Co, Sr in the precursor liquid, the catalyst was prepared by a one-step heating method.
It improves the catalytic activity and stability of acidic OER, reduces the overpotential and increases the electrochemically active surface area, and can maintain good performance for a long time.
Smart Images

Figure BDA0004965336980000071 
Figure BDA0004965336980000091 
Figure HDA0004965337000000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolytic water catalysis, and in particular to a cobalt, manganese and strontium ternary metal catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen production by water electrolysis consists of two half reactions, namely the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. Theoretically, the production of hydrogen by water electrolysis only requires a thermodynamic potential of 1.23 V. OER is an electrochemical reaction coupled with four electrons and four protons, which requires higher energy (i.e., higher overpotential) than HER to overcome the kinetic barrier. The acidic OER reaction plays a key role in the electrolysis of water in PEM (proton exchange membrane) electrolyzers. To date, a large number of non-precious metal electrocatalysts with high activity and stability have been studied to drive the acidic HER, including transition metal sulfides, phosphides, nitrides, and metal nanoparticles encapsulated in carbon materials. At present, people are also committed to designing and developing OER electrocatalysts to enhance electrode kinetics and stability. Now a variety of acidic OER catalysts have been reported, such as transition metal oxides, sulfides, selenides, and layered structure materials. However, most electrocatalysts cannot withstand strong acid environments and high anode potentials and are easily oxidized and dissolved. Currently, RuO2 and IrO2 are recognized as the most advanced acidic OER electrocatalysts, but they are both scarce precious metal materials and are unlikely to be applied on a large scale, which greatly limits the practical application of PEM electrolyzers for water electrolysis.
[0003] To solve this problem, one approach is to couple noble metal elements with transition metal (TM)-based oxides to produce compounds, such as IrW-W2B alloy catalysts, Ir-Mn oxides, IrO x / SrIrO3, etc. These compounds show good OER performance and improved stability in acid; another approach is to design and synthesize noble metal-free catalysts based on TM-based materials, which show excellent OER activity and stability in acidic media. However, they still lag behind the current advanced noble metal-based catalysts and are easily corroded by acids, so further improving their performance is crucial for their practical application.
[0004] Among many TM-based oxides, manganese oxide (MnO x ) has rich valence states and crystal structures, and shows excellent electrocatalytic performance in various electrochemical reactions. xAs an important member of the family, MnO2 has the potential to replace precious metals as an acidic OER catalyst due to its relatively high catalytic activity and stability. Early experiments showed that manganese oxides can act as efficient bifunctional electrocatalysts for ORR and OER under alkaline conditions. There are also a few reports on the use of manganese-based oxides in acidic oxygen evolution reaction, but the catalytic activity of most reported materials is limited to 10 mA cm -2 The overpotential under current density is usually greater than 500mV, so the activity of manganese-based materials for acidic OER reactions needs to be further improved. Synergistic effect engineering is an important strategy to improve the intrinsic activity of OER catalysts. Therefore, combining MnO2 with other non-precious metal-based oxides in many materials can inhibit the decomposition of MnO2 and stabilize the catalytic sites. This coupling strategy is an effective way to adjust the electronic structure of MnO2. It can optimize the adsorption and desorption energy of intermediates during the OER reaction, thereby significantly enhancing the intrinsic catalytic activity of the material. Among many transition metals, cobalt oxides have been proven to be highly active for OER in theory and experiment. Theoretical calculations show that the catalytic activity of Co3O4 is comparable to that of RuO2, but the catalyst is prone to corrosion during the OER process. Therefore, the development of Co catalysts for acidic OER still needs to pay attention to dissolution issues. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a cobalt-manganese-strontium ternary metal catalyst and its preparation method and application in view of the deficiencies in the prior art. The cobalt-manganese-strontium trimetallic oxide catalyst provided by the present invention has excellent acidic OER catalytic activity.
[0006] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0007] The invention provides a cobalt-manganese-strontium ternary metal catalyst, the material surface is rough and has holes, has three metal oxide phases of Mn, Co and Sr, namely MnO2, Co3O4 and SrO2, has a structure in which amorphous and crystalline phases coexist, and has a phase interface composed of a crystal plane and an amorphous plane.
[0008] According to the above scheme, Sr is distributed on the surface and inside of the catalyst; XRD diffraction characterizes the presence of SrO2 characteristic diffraction peaks, and strontium oxide SrO2 has good crystallinity.
[0009] According to the above scheme, the atomic ratio of Mn to Co in the above cobalt-manganese-strontium ternary metal catalyst is 3:1-5:1.
[0010] According to the above scheme, the atomic ratio of Co and Sr on the sample surface is 1:0.008-0.167.
[0011] A method for preparing a cobalt-manganese-strontium ternary metal catalyst comprises preparing a manganese source, a cobalt source solution and a strontium source substance to obtain a precursor solution; dropping the precursor solution on a pretreated conductive substrate, performing a heating reaction, and cooling to room temperature after the reaction is completed to obtain the cobalt-manganese-strontium ternary metal catalyst.
[0012] According to the above scheme, the conductive substrate is a carbon cloth substrate, and the carbon cloth substrate is pretreated by cutting the carbon cloth, soaking it in concentrated nitric acid, taking it out, and ultrasonically cleaning it with deionized water and anhydrous ethanol to obtain a pretreated carbon cloth substrate.
[0013] In the above scheme, the molar ratio of cobalt to strontium in step (2) is 6:1-120:1, preferably 12-100:1, and more preferably 20-100:1.
[0014] In the above scheme, the molar ratio of manganese to cobalt in step (2) is 3:1-5:1.
[0015] According to the above scheme, the manganese source material is manganese nitrate, the cobalt source material is cobalt nitrate, and the strontium source material is strontium chloride.
[0016] In the above scheme, the precursor droplets are placed on the pretreated carbon cloth substrate and heated on a heating plate for reaction.
[0017] In the above scheme, the temperature of the heating reaction in step (2) is 150-400°C and the time is 2-12h.
[0018] Application of the above-mentioned cobalt, manganese, strontium ternary metal catalyst in acidic OER catalysis.
[0019] The applicant's research found that after the introduction of Sr into MnCo metal oxide, the catalyst surface becomes rough and some holes appear, which is conducive to the full immersion of the electrolyte in the reaction and increases the electrochemical active surface area; at the same time, the introduction of Sr can induce electron transfer on the one hand, thereby increasing the content of high-valent Co, and the high-valent transition metal active sites will promote OER performance. In addition, the introduction of Sr can also inhibit the dissolution of Co to a certain extent, thereby improving the stability of the catalyst; on the other hand, the introduction of Sr can promote the increase of surface Co-OH groups, thereby accelerating the OER kinetics and having excellent OER catalytic activity.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The cobalt, manganese and strontium ternary metal catalyst provided by the invention has excellent acidic OER catalytic activity.
[0022] The invention provides a method for preparing a cobalt-manganese-strontium ternary metal catalyst. The method prepares a MnCoSr trimetallic catalyst by a one-step heating method by changing the ratio of Mn, Co and Sr in a precursor solution, and obtains MnCoSr trimetallic oxides with different Sr contents by changing the ratio of Mn, Co and Sr in the precursor solution. The method is convenient, simple and controllable, and the prepared catalyst has excellent acidic OER catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Scanning electron microscope (SEM) images of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 of the present invention and the MnCo oxide sample MCO2 prepared in Comparative Example 1, and the element distribution diagram of the MnCoSr trimetallic oxide.
[0024] Figure 2 Transmission electron microscope (TEM) images (ac) and EDX element mapping image (d) of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 of the present invention.
[0025] Figure 3 XRD patterns of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 of the present invention and the MnCo oxide sample MCO2 prepared in Comparative Example 1.
[0026] Figure 4 High-resolution XPS spectra of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 of the present invention and the MnCo oxide sample MCO2 prepared in Comparative Example 1.
[0027] Figure 5 The MnCoSr trimetallic oxide samples prepared in Examples 1-4 of the present invention and the oxide samples MCO2, MnO2, Co3O4, MnSrO prepared in Comparative Example 1 are x and CoSrO x OER performance test diagram.
[0028] Figure 6 This is the Faraday efficiency (FE) diagram of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 of the present invention.
[0029] Figure 7 The MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 of the present invention is an oxide sample of MCO2, MnO2, Co3O4, MnSrO x 、CoSrO x The scan rates in the OER performance test were 20, 40, 60, 80, 100, and 120 mV s -1 CV curve when .
[0030] Figure 8 The MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 of the present invention is an oxide sample of MCO2, MnO2, Co3O4, MnSrO x 、CoSrO x Fitting curve of capacitance current and scan rate in OER performance test (a) and LSV curve normalized by electrochemical active specific surface area (b).
[0031] Fig. 9 SEM spectra (ac) and EDS spectra (d) of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 of the present invention and the MnCo oxide sample MCO2 prepared in Comparative Example 1 after OER performance stability test.
[0032] Fig.10 XRD spectra and Raman spectra of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 of the present invention and the MnCo oxide sample MCO2 prepared in Comparative Example 1 after OER performance stability test.
[0033] Fig.11 XPS spectrum of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 of the present invention after OER performance stability test. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0035] In a specific embodiment, the carbon cloth cyber electrochemical material W0S1011 used; 50% manganese nitrate solution (Mn(NO3)2), cobalt nitrate (Co(NO3)2·6H2O), strontium chloride (SrCl2·6H2O), and anhydrous ethanol are all analytically pure and purchased from Sinopharm Chemical Reagent Co., Ltd.; concentrated nitric acid (HNO3) is of premium grade and purchased from Sinopharm Chemical Reagent Co., Ltd.
[0036] Example 1
[0037] A method for preparing a cobalt-manganese-strontium ternary metal catalyst comprises the following steps:
[0038] (1) Pretreatment of carbon cloth substrate
[0039] A carbon cloth of 2 cm × 2 cm in size was cut out and soaked in a beaker containing 100 mL of concentrated nitric acid for 48 h. Then, it was ultrasonically treated with deionized water and anhydrous ethanol for 30 min respectively to remove the oxide on the surface, thereby obtaining a pretreated carbon cloth substrate.
[0040] (2) Preparation of MnCoSr oxide
[0041] First, 9.3 mL of 50% manganese nitrate solution, 0.01 mol Co(NO3)2·6H2O, and 0.1 mmol SrCl2·6H2O were dissolved in 10.7 mL of deionized water and stirred for 30 min to form a uniform solution as the precursor solution. The precursor solution was pipetted at 150 μL·cm -2 An amount of MCSO was dropped on the pretreated carbon cloth substrate and reacted on a hot plate at 250°C for 5.5 hours. After the reaction was completed and cooled to room temperature, MnCoSr oxide was obtained, named MCSO1, as a cobalt, manganese, and strontium ternary metal catalyst.
[0042] Example 2
[0043] A method for preparing a cobalt-manganese-strontium ternary metal catalyst comprises the following steps:
[0044] (1) Pretreatment of carbon cloth substrate
[0045] A carbon cloth of 2 cm × 2 cm in size was cut out and soaked in a beaker containing 100 mL of concentrated nitric acid for 48 h. Then, it was ultrasonically treated with deionized water and anhydrous ethanol for 30 min respectively to remove the oxide on the surface, thereby obtaining a pretreated carbon cloth substrate.
[0046] (2) Preparation of MnCoSr oxide
[0047] First, 9.3 mL of 50% manganese nitrate solution, 0.01 mol Co(NO3)2·6H2O, and 0.4 mmol SrCl2·6H2O were dissolved in 10.7 mL of deionized water and stirred for 30 min to form a uniform solution as the precursor solution. The precursor solution was pipetted at 150 μL·cm -2 An amount of MCSO was dropped onto the pretreated carbon cloth substrate and reacted on a hot plate at 250°C for 5.5 hours. After the reaction was completed and cooled to room temperature, MnCoSr oxide was obtained, named MCSO2, as a cobalt, manganese, and strontium ternary metal catalyst.
[0048] Example 3
[0049] A method for preparing a cobalt-manganese-strontium ternary metal catalyst comprises the following steps:
[0050] (1) Pretreatment of carbon cloth substrate
[0051] A carbon cloth of 2 cm × 2 cm in size was cut out and soaked in a beaker containing 100 mL of concentrated nitric acid for 48 h. Then, it was ultrasonically treated with deionized water and anhydrous ethanol for 30 min respectively to remove the oxide on the surface, thereby obtaining a pretreated carbon cloth substrate.
[0052] (2) Preparation of MnCoSr oxide
[0053] First, 9.3 mL of 50% manganese nitrate solution, 0.01 mol Co(NO3)2·6H2O, and 0.8 mmol SrCl2·6H2O were dissolved in 10.7 mL of deionized water and stirred for 30 min to form a uniform solution as the precursor solution. The precursor solution was pipetted at 150 μL·cm -2 An amount of MCSO was dropped onto the pretreated carbon cloth substrate and reacted on a hot plate at 250°C for 5.5 hours. After the reaction was completed and cooled to room temperature, MnCoSr oxide was obtained, named MCSO3, as a cobalt, manganese, and strontium ternary metal catalyst.
[0054] Example 4
[0055] A method for preparing a cobalt-manganese-strontium ternary metal catalyst comprises the following steps:
[0056] (1) Pretreatment of carbon cloth substrate
[0057] A carbon cloth of 2 cm × 2 cm in size was cut out and soaked in a beaker containing 100 mL of concentrated nitric acid for 48 h. Then, it was ultrasonically treated with deionized water and anhydrous ethanol for 30 min respectively to remove the oxide on the surface, thereby obtaining a pretreated carbon cloth substrate.
[0058] (2) Preparation of MnCoSr oxide
[0059] First, 9.3 mL of 50% manganese nitrate solution, 0.01 mol Co(NO3)2·6H2O, and 1.5 mmol SrCl2·6H2O were dissolved in 10.7 mL of deionized water and stirred for 30 min to form a uniform solution as the precursor solution. The precursor solution was pipetted at 150 μL·cm -2 An amount of MCSO was dropped onto the pretreated carbon cloth substrate and reacted on a hot plate at 250°C for 5.5 hours. After the reaction was completed and cooled to room temperature, MnCoSr oxide was obtained, named MCSO4, as a cobalt, manganese, and strontium ternary metal catalyst.
[0060] Comparative Example
[0061] (1) Pretreatment of carbon cloth substrate
[0062] A carbon cloth of 2 cm × 2 cm in size was cut out and soaked in a beaker containing 100 mL of concentrated nitric acid for 48 h. Then, it was ultrasonically treated with deionized water and anhydrous ethanol for 30 min respectively to remove the oxide on the surface, thereby obtaining a pretreated carbon cloth substrate.
[0063] (2) Preparation of MnCo oxide
[0064] First, 9.3 mL of 50% manganese nitrate solution and 0.01 mol Co(NO3)2·6H2O were dissolved in 10.7 mL of deionized water and stirred for 30 min to form a uniform solution as the precursor solution. The precursor solution was pipetted at 150 μL·cm -2 An amount of MnCo was dropped on the pretreated carbon cloth substrate and reacted on a hot plate at 250°C for 5.5 hours. After the reaction was completed and cooled to room temperature, MnCo oxide was obtained, named MCO2.
[0065] (3) Preparation of Mn oxide
[0066] First, 9.3 mL of 50% manganese nitrate solution was dissolved in 10.7 mL of deionized water and stirred for 30 min to form a uniform solution as the precursor solution. The precursor solution was pipetted at 150 μL·cm -2 An amount of Mn was dropped on the pretreated carbon cloth substrate and reacted on a hot plate at 250°C for 5.5 hours. After the reaction was completed and cooled to room temperature, Mn oxide was obtained, named MnO2.
[0067] (4) Preparation of Co oxide
[0068] First, 0.01 mol Co(NO3)2·6H2O was dissolved in 20 mL of deionized water and stirred for 30 min to form a uniform solution as the precursor solution. The precursor solution was pipetted at 150 μL·cm -2 An amount of 200 μg / ml was dropped onto the pretreated carbon cloth substrate and reacted on a hot plate at 250 °C for 5.5 h. After the reaction was completed and cooled to room temperature, Co oxide was obtained, named Co3O4.
[0069] (5) Preparation of MnSr oxide
[0070] First, 9.3 mL of 50% manganese nitrate solution and 0.4 mmol SrCl2·6H2O were dissolved in 10.7 mL of deionized water and stirred for 30 min to form a uniform solution as the precursor solution. The precursor solution was pipetted at 150 μL·cm -2 The amount of MnSr was dropped onto the pretreated carbon cloth substrate and reacted on a hot plate at 250 °C for 5.5 h. After the reaction was completed and cooled to room temperature, MnSr oxide was obtained, named MnSrO x .
[0071] (6) Preparation of CoSr oxide
[0072] First, 0.01 mol Co(NO3)2·6H2O and 0.4 mmol SrCl2·6H2O were dissolved in 20 mL of deionized water and stirred for 30 min to form a uniform solution as the precursor solution. The precursor solution was pipetted at 150 μL·cm -2 The amount of 200 μg / ml was dropped onto the pretreated carbon cloth substrate and reacted on a hot plate at 250 °C for 5.5 h. After the reaction was completed and cooled to room temperature, CoSr oxide was obtained, named CoSrO x .
[0073] Test Example 1
[0074] This test is used to illustrate the microscopic morphology of the cobalt, manganese and strontium ternary metal catalyst material of the present invention.
[0075] Figure 1 The electron scanning microscope (SEM) images (ad) of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 and the MnCo oxide sample MCO2 prepared in the comparative example and the element distribution diagram (e) of the MnCoSr trimetallic oxide, wherein (a) and (b) are SEM images of MCO2, and (c) and (d) are SEM images of MCSO2. Figure 1 It can be seen that the MnCo bimetallic oxide material presents a smooth block structure; after the introduction of Sr metal to obtain the MnCoSr trimetallic oxide, the surface of the material becomes rough and large holes appear. The appearance of holes is also conducive to the full immersion of the electrolyte in the reaction and increases the electrochemical active surface area. The micro-area surface of the MnCoSr trimetallic oxide sample was scanned and tested by EDS to obtain the EDS-mapping element mapping diagram. Figure 1 (e) It shows that the Mn, Co, Sr, and O elements are evenly distributed on the surface of MCSO2, and the atomic percentage of Mn and Co elements is close to 4:1, indicating that the introduction of Sr does not affect the formation of Mn and Co oxides, while the Sr element content is relatively low. This may be because most of the Sr oxides are deposited inside the sample, while the Sr content on the surface is relatively low. The atomic percentages of the elements on the surface of MCO2 and MCSO2 samples are shown in Table 1.
[0076] Table 1
[0077]
[0078] Test Example 2
[0079] This test is used to illustrate the microstructure of the cobalt-manganese-strontium ternary metal catalyst material of the present invention.
[0080] Figure 2 Transmission electron microscope (TEM) images (ac) and EDX element mapping image (d) of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2. Figure 2 It can be seen from the HRTEM images of (a), (b) and (c) that there are lattice fringes with lattice spacings of 0.45nm and 0.29nm, respectively, corresponding to the (004) and (211) crystal planes of MnO2; the lattice fringes with a lattice spacing of 0.24nm correspond to the (400) crystal plane of Co3O4; the lattice fringes with lattice spacings of 0.26nm and 0.25nm correspond to the (202) and (113) crystal planes of SrO2. Figure 2 The obvious layered structure in (b) shows that the bulk structure of MCSO2 is formed by the stacking of three mixed metal oxides layer by layer. In summary, MCSO2 is composed of three metal oxides: MnO2, Co3O4, and SrO2. In addition, it can be found that MCSO2 exhibits a structure in which amorphous and crystalline phases coexist, with a phase interface composed of crystal planes and amorphous planes. The existence of this interface is conducive to optimizing the adsorption of intermediates and the transfer of electrons in the OER process, thereby improving the intrinsic activity of the material. In addition, the presence of the amorphous phase has a certain positive effect on improving the stability of the reaction system.
[0081] Test Example 3
[0082] This test is used to illustrate the physical phase and crystal structure of the cobalt, manganese and strontium ternary metal catalyst material of the present invention.
[0083] Figure 3 The XRD patterns of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 and the MnCo oxide sample MCO2 prepared in the comparative example are shown in FIG. Figure 3 It can be seen that the diffraction peaks at 27.5°, 35.7°, and 59.6° belong to SrO2 (PDF#3-872). Compared with the diffraction peaks of MnO2 and Co3O4, the peaks belonging to SrO2 are sharper and more intense, indicating that strontium oxide has better crystallinity among the three metal oxides.
[0084] Figure 4 The high-resolution XPS spectra of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 and the MnCo oxide sample MCO2 prepared in Comparative Example 1. Figure 4 (a) is the high-resolution XPS spectrum of Mn 2p, where the two peaks at 642.40 eV and 654.10 eV correspond to Mn 2p 3 / 2 and Mn 2p 1 / 2 Deconvolution is performed on the two orbitals, which can be fitted to Mn 4+ (644.35eV, 654.64eV) and Mn3+ (642.36eV, 653.65eV). The spin-orbit splitting energy difference of Mn 2p is 11.7eV, which is consistent with that of MnO2 reported in some literature. Figure 4 (b) is the high-resolution XPS spectrum of Co 2p. The two peaks at 780.62 eV and 795.63 eV in the MCSO2 sample correspond to Co 3+ Co 2p 3 / 2 and Co 2p 1 / 2 The two peaks at 782.42 eV and 797.23 eV correspond to Co 2+ Co 2p 3 / 2 and Co 2p 1 / 2 Spin orbit. Compared with MCO2 sample, MCSO2 sample belongs to Co 2+ The peak of Co has a shift of about +0.48 eV, which proves the regulatory effect of the introduction of Sr on its electronic coordination environment. 3+ / Co 2+ The atomic ratio can be obtained by calculating the relative area of the fitting curve. 3+ With Co 2+ The peak area ratio is 1.45:1, while the Co 3+ With Co 2+ The peak area ratio is 1.01:1, which further illustrates that the introduction of Sr can induce electron transfer, thereby increasing the content of high-valent Co, and the high-valent transition metal active sites will promote the OER performance. Figure 4 (c) is the high-resolution XPS spectrum of Sr 3d, which can be fitted into two double peaks. The double peak with lower binding energy (133.62eV, 135.44eV) corresponds to Sr in the SrO2 lattice, while the double peak with higher binding energy (134.60eV, 136.75eV) may come from some Sr on the surface, such as Sr(OH)2 and Sr(NO3)2. Figure 4 (d) is the high-resolution XPS spectrum of O1s, which can be divided into three peaks by fitting. The peak at 530.08eV corresponds to the lattice oxygen in the three oxides, the peak at 531.41eV corresponds to the hydroxyl group in the water molecules adsorbed on the surface, and the peak at 532.92eV corresponds to the water adsorbed on the sample surface. In summary, the above analysis shows that the introduction of Sr elements can effectively adjust the electronic structure of the material, thereby promoting electron transfer in the OER process and effectively improving the electrocatalytic activity of the sample.
[0085] Test Example 4
[0086] This test is used to illustrate the OER performance of the cobalt, manganese and strontium ternary metal catalyst material of the present invention.
[0087] In 0.5 mol / L H2SO4, a three-electrode system was used on a CHI660E workstation to measure the MnCoSr trimetallic oxide samples prepared in Examples 1-4 and the oxide samples MCO2, MnO2, Co3O4, MnSrO x and CoSrO x OER performance evaluation was performed. Figure 5 (a) Linear sweep voltammogram (LSV) of MnCoSr trimetallic oxide prepared with different proportions of Sr in the precursor solution; Figure 5 (b) MCO2, MnO2, Co3O4, MnSrO x 、CoSrO x and linear sweep voltammograms (LSV) of MCSO2; Figure 5 (c) MCO2, MnO2, Co3O4, MnSrO x 、CoSrO x and Tafel curve of MCSO2; Figure 5 (d) MCO2, MnO2, Co3O4, MnSrO x 、CoSrO x and electrochemical impedance spectroscopy (EIS) of MCSO2; Figure 5 (e) MCO2, MnO2, Co3O4, MnSrO x 、CoSrO x OER stability test curve of MCSO2 at constant current density. Figure 5 As shown in (a), the MCSO2 sample has the highest OER catalytic performance at 10 mA cm -2 At a current density of , its overpotential is 332mV, which is better than MCO2 (393mV). Figure 5 (b) shows that the double metal oxide MnSrO x 、CoSrO x Compared with MCO2, MCSO2 has the best OER performance and is significantly better than single metal oxides, which shows that the synergistic effect between the three metal mixed oxides makes the material show excellent performance. Figure 5 (c) The Tafel slope of MCOS2 (58.9mV dec -1 ) is significantly lower than other comparative samples, indicating that it has faster reaction kinetics. Figure 5 As shown in (d), MCSO2 has the smallest R ct , indicating that its charge transfer rate is the fastest during the reaction, which is beneficial to the enhancement of OER activity. Figure 5 (e) The results of different samples at 10 mA cm -2Vt change curve under current density. It can be seen that in the 100-hour stability test, MCSO2 maintained good performance, proving its good stability in acidic OER and also showing its application prospects and value in the electrolytic acidic water oxygen evolution reaction.
[0088] In order to test the selectivity of MCSO2 for O2 in acidic electrolyte, it was placed in an H-type electrolytic cell for water electrolysis OER reaction, and the products at the working electrode end were collected for gas chromatography detection. The Faradaic efficiency (FE) results are shown in Figure 6 As shown. The oxygen in the product was detected by GC, and the average FE value of O2 was 95.3%, which proved the excellent OER selectivity of the MCSO2 sample during the reaction.
[0089] Figure 7 (af) are MnO2, Co3O4, MnSrO x 、CoSrO x The voltammetric cycle curves of MCO2 and MCSO2 can be used to calculate the double layer capacitance (Cdl) of each sample. Figure 8 Figure 1 is the fitting diagram of capacitance current and scan rate (a) and the LSV curve normalized by electrochemical active surface area (ECSA). Figure 8 As shown in (a), the MCOS2 sample has the highest Cdl of 343.5 μF·cm compared with other samples. -2 , indicating that the introduction of Sr can effectively increase the electrochemical active surface area (ECSA) of the material and provide more reactive sites for the OER reaction. From the normalized LSV obtained after normalization, it can be seen that MCSO2 has the highest intrinsic activity in addition to the increased number of active sites. In addition, the normalized LSV of MnO2 and Co3O4 is not much different from that of MnSrOx and CoSrOx. It can be further speculated that Sr does not act as a reactive site in them, but mainly plays a role in regulating the material structure.
[0090] Test Example 5
[0091] This test is used to illustrate the morphology and structure of the cobalt, manganese and strontium ternary metal catalyst material of the present invention after the OER performance stability test.
[0092] Fig. 9 The SEM spectra (ac) and EDS spectra (d) of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 and the MnCo oxide sample MCO2 prepared in Comparative Example 1 after OER performance stability test. Fig. 9(ac) It can be seen that after the stability test, large cracks appeared on the surface of MnCo bimetallic oxide (MCO2), indicating that its bulk structure was corroded by sulfuric acid during the reaction process. In contrast, the bulk structure of MnCoSr trimetallic oxide (MCOS2) remained relatively intact, proving that the sample had good stability. Many large holes and white granular precipitation appeared on the surface of the sample, which may be because the SrO2 deposited inside the sample precipitated in the form of strontium salt (SrSO4). Table 2 shows the atomic percentage of surface elements before and after the sample test. It can be seen that after the stability test of MCO2, Mn:Co changed from 4.02:1 to 9.95:1, indicating that the attenuation of its performance came from the dissolution of Co during the reaction process; and after the stability test of MCSO2, Mn:Co:Sr changed from 4.14:1:0.048 to 6:1:0.22, indicating that the introduction of Sr can inhibit the dissolution of Co to a certain extent, thereby improving the stability of the material, and the increase in Sr content may be due to the precipitation of Sr inside the sample.
[0093] Table 2
[0094]
[0095] Fig.10 XRD and Raman spectra of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 and the MnCo oxide sample MCO2 prepared in the comparative example after OER performance stability test. Fig.10 From the XRD comparison of (a), it can be seen that there is no obvious change in the XRD peak before and after the performance test, which proves that the sample structure is relatively stable during the reaction process. Fig.10 (b) Raman comparison shows that MCSO2 reacts at 456 cm -1 A peak appeared at , indicating that a phase change occurred on the surface of Co3O4 during the reaction, and Co-OH groups were formed, which can increase more active sites for the OER reaction to promote the release of O2. In contrast, MCO2 did not undergo a phase change during the reaction, which shows that the introduction of Sr can promote the increase of surface Co-OH groups, thereby accelerating the OER kinetics.
[0096] Fig.11 XPS spectrum of the MnCoSr trimetallic oxide sample MCSO2 prepared in Example 2 after OER performance stability test. Fig.11 (a) and (b) show that the characteristic peak values of the Mn 2p and Co 2p high-resolution XPS spectra did not change significantly after the performance test, indicating the stability of the MnO2 and Co3O4 structures inside the sample MCSO2 during the reaction process. Fig.11(c) is the high-resolution XPS spectrum of Sr 3d. The Sr content in the lattice and the surface Sr content can be compared by calculating the relative area of the fitting curve. It can be seen from the figure that the surface Sr content increases after the performance test, which further proves that SrO2 will gradually precipitate during the reaction, which is consistent with the previous analysis. The precipitation of SrO2 inside the sample will lead to some larger holes on the surface of the material, which is conducive to increasing the electrochemical active surface area of the material, thereby improving the activity of the sample; on the other hand, the alkaline earth metal Sr leached in the reaction can form a loose structure, and then collapse accordingly, collapsing into an amorphous structure, which is also conducive to improving the OER activity and stability in acidic media.
[0097] In summary, the cobalt-manganese-strontium ternary metal catalyst provided by the present invention has excellent acidic OER catalytic activity. -2 It has excellent performance at a current density of 332 mV, with an overpotential of 332 mV, and can run continuously for 100 hours; CV, EIS and other tests show that the cobalt, manganese and strontium ternary metal catalyst sample has a larger electrochemically active surface area, smaller electrochemical impedance and higher intrinsic activity, which is more conducive to the OER reaction. This work provides a new solution for the development of efficient and stable acidic OER catalysts.
[0098] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A cobalt-manganese-strontium ternary metal catalyst, characterized in that: The surface of the cobalt-manganese-strontium ternary metal catalyst material is rough and has holes. It has three metal oxide phases of Mn, Co, and Sr, namely MnO2, Co3O4, and SrO2. It has a structure in which amorphous and crystalline phases coexist and has a phase interface composed of crystal planes and amorphous planes.
2. The cobalt-manganese-strontium ternary metal catalyst according to claim 1, characterized in that: Sr is distributed on the surface and inside of the catalyst, and strontium oxide SrO2 has good crystallinity.
3. The cobalt-manganese-strontium ternary metal catalyst according to claim 1, characterized in that: The atomic ratio of Mn and Co in the cobalt-manganese-strontium ternary metal catalyst is 3:1-5:
1.
4. The cobalt-manganese-strontium ternary metal catalyst according to claim 1, characterized in that: The atomic ratio of Co and Sr on the sample surface is 1:0.008-0.
167.
5. The method for preparing the cobalt-manganese-strontium ternary metal catalyst according to claim 1, characterized in that: A precursor solution is prepared by mixing a manganese source, a cobalt source solution and a strontium source substance; the precursor solution is dropped on a pretreated conductive substrate, heated to react, and after the reaction is completed and cooled to room temperature, the cobalt-manganese-strontium ternary metal catalyst is obtained.
6. The preparation method according to claim 5, characterized in that: The molar ratio of cobalt to strontium is 6:1-120:1; the temperature of the heating reaction is 150-400°C, and the time is 2-12 hours.
7. The preparation method according to claim 5, characterized in that: The molar ratio of cobalt to strontium is 12-100:
1.
8. The preparation method according to claim 5, characterized in that: The molar ratio of manganese to cobalt in step (2) is 3:1-5:
1.
9. The preparation method according to claim 5, characterized in that: The manganese source material is manganese nitrate, the cobalt source material is cobalt nitrate, and the strontium source material is strontium chloride; the conductive substrate is a carbon cloth substrate, and the carbon cloth substrate is pretreated by cutting the carbon cloth, soaking it in concentrated nitric acid, taking it out, and ultrasonically cleaning it with deionized water and anhydrous ethanol to obtain the pretreated carbon cloth substrate.
10. Use of the cobalt-manganese-strontium ternary metal catalyst according to any one of claims 1 to 4 in acidic OER catalysis.
Citation Information
Patent Citations
Preparation method of strontium-improved nickel-cobalt-manganese ternary material
CN107579226A
Low-cost acid medium oxygen evolution catalyst and synthesis method thereof
CN117364125A
Rare earth element doped cobalt manganese oxide-based catalyst and preparation and application thereof
CN117904667A